WOMEN’S ENDLESS SUFFERINGS IN MUNA MASYARI’S DAMAR KAMBANG - Okta Feri, Zefki; Khoshimov, Maksud (Universitas Negeri Yogyakarta, 2023)
Violence against women is still a hot issue in society and continues to receive a lot of attention, especially from women and human rights observers. In addition to legalizing the rule of law for the protection and equalization of women's rights, efforts to increase awareness and understanding of the importance of gender equality in all aspects are continuing. One of them is through literary works, such as Damar Kambang by Muna Masyari (2020). Through the approach of Feminists Literary Criticism, this study attempts to investigate forms of gender violence against female characters in the novel. This research also explores the perpetrators of these crimes and the factors causing violence and suffering to these female characters. The results show that there are three forms of violence against women in the novel, namely physical violence such as beatings, slapping, and shackles; emotional violence such as swearing and betting on women in gambling; and sexual violence in the form of rapes. The violent perpetrators were the closest relatives of the victim, such as the father, future husband, husband, and brother-in-law. Patriarchal power giving full power to men, including the social environment based on patriarchal power, is suspected to be the main factor in the occurrence of these various forms of violence. In addition, the rigid customary law that places men above all else also contributes to this problem. This research shows that there are still many acts of violence against women, so this issue needs serious attention from all parties.